The impact of the radical urbanization index on depression risk among middle-aged and elderly Chinese: Evidence from a large-scale cross-sectional study - Yuting Li; Diege Long; Zhen Ye (PLoS ONE, 2026)
Background Rapid urbanization in China, while boosting socioeconomic development, has triggered “radical urbanization” characterized by land expansion outpacing population growth and economic activity. This spatial mismatch manifests as high building vacancy rates and underutilized infrastructure. Although urbanization is linked to mental health outcomes, evidence on radical urbanization’s impact on depression—especially among middle-aged and elderly populations—remains scarce. Methods This cross-sectional study utilized 2011 baseline data from the China Health and Retirement Longitudinal Study (CHARLS), including 11,126 participants aged ≥45 years. Depressive symptoms were assessed using the CES-D scale (score ≥10 = clinically significant). The radical urbanization index was calculated as the log ratio of city-level built-up area (from China City Statistical Yearbook) to aggregated nighttime light DN values (using thresholds: eastern China ≥34, western China ≥25). Multivariable logistic regression (three adjusted models) and restricted cubic splines evaluated associations. Subgroup analyses and machine learning models (AUC comparison) further validated findings. Results (1) Radical urbanization index was significantly higher in the depressive symptoms (DS) group vs. non-depressive symptoms (NDS) group (−4.74 vs. −4.96, *p* < 0.001). (2) Each 1-unit increase in the index elevated depression risk by 26% (OR=1.26, 95% CI:1.14–1.38; fully adjusted Model 3). (3) A dose-response relationship emerged: Q4 (highest index) had 1.68 × higher depression risk than Q1 (lowest) (*p*-trend<0.001). (4) Stronger associations occurred in central/western China (e.g., Hunan, Sichuan), low-education groups (OR=1.31), and rural residents (OR=1.30). (5) Adding the index to prediction models improved test-set AUC from 0.649 to 0.663. Conclusion Radical urbanization—reflecting inefficient land-use and economic-population mismatch—is independently associated with depression among Chinese middle-aged and elderly adults. Findings underscore the need to reorient urbanization policies from “land expansion” to “human-centered” development to mitigate mental health burdens.